ANALISIS FINANCIAL DISTRESS PERUSAHAAN SUB SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Legowo Dwi Resihono; Retnoningrum; Luluk Takari; Sri Hutami (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the effect of financial ratios on the probability of financial distress among construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. Financial distress refers to a condition in which a company experiences financial difficulties before reaching bankruptcy, often characterized by liquidity problems and excessive leverage. The independent variables used in this study are the Current Ratio (CR), Debt to Asset Ratio (DAR), Fixed Asset Turnover (FATO), Profit Margin (PM), and Sales Growth (SG), while financial distress (FD) serves as the dependent variable measured using the Modified Altman Z″-Score model. The research adopts a quantitative explanatory approach with secondary data obtained from annual financial reports of 21 construction companies for three consecutive years, resulting in 63 firm-year observations. Logistic regression analysis is employed using SPSS version 19 to evaluate both partial and simultaneous effects of financial ratios on financial distress. The results indicate that, simultaneously, all independent variables have a significant effect on the likelihood of financial distress, demonstrating that financial ratios can serve as an early warning system for corporate financial health. Partially, only the Debt to Asset Ratio (DAR) shows a significant positive effect on financial distress, suggesting that higher leverage increases the probability of financial failure. Meanwhile, CR, FATO, PM, and SG have negative but statistically insignificant effects. The model exhibits excellent goodness of fit, with a Nagelkerke R² value of 0.917, Hosmer–Lemeshow significance of 0.976, and Omnibus test significance of 0.000. Overall, the findings highlight that capital structure (leverage) is the key determinant of financial distress in Indonesian construction firms. Proper debt management, efficient cash flow control, and sustainable financial policies are essential to maintain business continuity and minimize the risk of financial distress, especially during periods of economic uncertainty. Keywords: Financial distress, Altman Z-Score, Liquidity, Leverage, Profitability, Sales Growth, Construction Sector.